Environmental Health Risk Analysis of Legundi Leaf Essential Oil Toxicity (Vitex Trifolia L.) - Ni Luh Putu Putri Setianingsih; Ni Made Ayu Suardani Singapurwa; Gede Yohanes Arygunartha; Sang Ayu Made Agung Prasetiawati Djelantik; I Wayan Winduyasa (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Caring for the environment means participating in preserving the environment as well as possible, one concern for the environment is regarding the development of the use of natural materials. This is done to ensure the safety of consumers' use of herbal medicinal products or food products. One of the plants that are often used for traditional medicine is the legundi plant (Vitex trifolia L.). Legundi leaf essential oil is used for humans for environmental health and food products. Methods: Samples of legundi leaves were collected in stages from the Sukawati Gianyar area. Furthermore, essential oil isolation was carried out using the maceration method, then a shrimp larvae toxicity test was carried out, then analysis was carried out by Gas Chromatography-Mass Spectroscopy (GC-MS). Results and Discussion: Toxicity test analysis show that the essential oil of legundi leaves has an LC50 value of 51,541 ppm, so it can be said that legundi leaf essential oil is toxic. GC results obtained eight chromatogram peaks. Of the eight peaks, there was one peak of the compound with 41.77% of the high area, namely the compound furan-2-carboxaldehyde. Conclusion: Legundi leaf essential oil is toxic, so this finding is important for developing science in environmental health and food product development. Environmental Health is used to increase public knowledge in the field of the utilization of food products.